2012
DOI: 10.5614/itbj.eng.sci.2012.44.3.6
|View full text |Cite
|
Sign up to set email alerts
|

The Power Consumption Performance of an Orbiting Screw Solid-Solid Mixer

Abstract: In this work we have investigated mixing in a modified orbiting screw mixer (MOSM) designed for solid-solid mixing. Mixing was carried out using urea powder and natural zeolite powder (UZ) of three varying particle sizes (50-60, 60-80 and 80 mesh). Power consumption was calculated from the measured torque of orbit and screw, obtained from computerized records. It was found that the mixing process in the modified orbiting screw mixer with air injection required a lower power consumption for each particle-size g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Laplante et al and Chong et al both showed that reducing the injection concentration (% of active ingredient in the demulsifier solution) improves demulsifier performance and that mixing depends on both the rate of energy dissipation and the mixing time. These two variables can be combined to give a single scaling variable, the mixing energy ( J = ε× t mix ). The mixing energy ( J ) can be estimated and/or directly measured for various vessels, mixers, pipes, and pumps . It allows a translation of mixing conditions from batch (mixing time × energy dissipation rate) to continuous (residence time × energy dissipation rate) processes.…”
Section: Introductionmentioning
confidence: 99%
“…Laplante et al and Chong et al both showed that reducing the injection concentration (% of active ingredient in the demulsifier solution) improves demulsifier performance and that mixing depends on both the rate of energy dissipation and the mixing time. These two variables can be combined to give a single scaling variable, the mixing energy ( J = ε× t mix ). The mixing energy ( J ) can be estimated and/or directly measured for various vessels, mixers, pipes, and pumps . It allows a translation of mixing conditions from batch (mixing time × energy dissipation rate) to continuous (residence time × energy dissipation rate) processes.…”
Section: Introductionmentioning
confidence: 99%
“…Для визначення впливу модифікації гвинтових конвеєрів на траєкторію переміщення частинок окремих компонентів використано метод дискретних елементів [10][11][12], математичне моделювання [13][14][15] та експериментальні дослідження [16][17].…”
unclassified